The economic impact of rheumatic heart disease in developing countries. (March 2015) - Watkins, D; Daskalakis, A
Abstract: Background: Rheumatic heart disease (RHD) is a neglected disease of poverty that is the most common paediatric cardiovascular condition in developing countries. Most RHD deaths occur in children and working-age adults, in whom the economic impact of premature death is high. Despite RHD being a preventable disease, global research and development funding for RHD was recently estimated at US$1·7 million, or about 0·1% of all global health funding. Decisions to scale up costly medical and surgical interventions for RHD are hindered, in part, by lack of evidence for the so-called return on investment that could be achieved through prevention of RHD-related mortality. We conducted a modelling study using data from 107 countries to estimate the economic impact of excess mortality from RHD. Methods: We used the full income approach to quantify the economic losses from RHD in 107 countries where the disease is endemic during 2010. Our analysis synthesised data from the Global Burden of Disease 2010 study, WHO life tables, UN population estimates, and World Bank macroeconomic indicators such as gross domestic product (GDP) per capita that are used in full-income calculations. We used the RHD mortality pattern in Costa Rica in 2010 as a baseline from which to define excess mortality. Data from this country were used because of Costa Rica's demonstrated success in controlling RHD in previous decades as well as its health system's resilience under political and economic constraints. We reported costs discounted at 3% yearly as well as undiscounted. Findings: We noted that the cost of the approximately 222 000 excess deaths from RHD in 2010 was around US$ (2014) 2·2 trillion (discounted) or US$5·4 trillion (undiscounted). Most of the economic burden of RHD was in countries with large populations in south Asia and east Asia. Our estimates were roughly proportional to those reported in a full-income study of HIV/AIDS mortality in sub-Saharan Africa, although our estimates were 10–100 times higher than those obtained using other economic methods, such as multiples of GDP per capita per disability-adjusted life-year. Interpretation: RHD continues to exert massive economic effects globally, mainly because of premature death in children and working-age adults. The economic cost of RHD in developing countries is over a million times higher than current donor funding levels. Our estimates suggest that careful increases in public-sector and private-sector spending on effective RHD prevention and control measures could provide impressive returns on investment. Future work will compare the full-income results to other economic evaluation methods such as those recommended by the Commission on Macroeconomics and Health. Our results could be the basis for benefit-cost analyses of medical and surgical interventions in resource-limited countries. Funding: None.